Constraining the Late Pleistocene history of the Laurentide Ice Sheet by dating the Missinaibi Formation, Hudson Bay Lowlands, Canada. (15th August 2016) - Dalton, April S.; Finkelstein, Sarah A.; Barnett, Peter J.; Forman, Steven L.
Abstract: Well-dated paleorecords from periods prior to the Last Glacial Maximum (LGM) are important for validating models of ice sheet build-up and growth. However, owing to glacial erosion, most Late Pleistocene records lie outside of the previously glaciated region, which limits their ability to inform about the dynamics of paleo-ice sheets. Here, we evaluate new and previously published chronology data from the Missinaibi Formation, a Pleistocene-aged deposit in the Hudson Bay Lowlands (HBL), Canada, located near the geographic center of the Laurentide Ice Sheet (LIS). Available radiocarbon (AMS = 44, conventional = 36), amino acid (n = 13), uranium-thorium (U-Th, n = 14), thermoluminescence (TL, n = 15) and optically stimulated luminescence (OSL, n = 5) data suggest that an ice-free HBL may have been possible during parts of Marine Isotope Stage 7 (MIS 7; ca. 243, 000 to ca. 190, 000 yr BP), MIS 5 (ca. 130, 000 to ca. 71, 000 yr BP) and MIS 3 (ca. 29, 000 to ca. 57, 000). While MIS 7 and MIS 5 are well-documented interglacial periods, the development of peat, forest bed and fluvial deposits dating to MIS 3 (n = 20 radiocarbon dates; 4 TL dates, 3 OSL dates), suggests that the LIS retreated and remained beyond, or somewhere within, the boundaries of the HBL during this interstadial. Ice sheet models approximate the margin of the LIS to Southern Ontario during this time, which is 700 km south of the HBL. Therefore, if correct, our data help constrain a significantly different configuration and dynamicity for the LIS than previously modelled. We can find no chronological basis to discount the MIS 3 age assignments. However, since most data originate from radiocarbon dates lying close to the reliable limit of this geochronometer, future work on dating the Missinaibi Formation using other geochronological methods (e.g. U-Th, OSL) is necessary in order to confirm the age estimates and strengthen the boundaries of the LIS during this period. Highlights: Synthesis of pre-LGM chronology data from the central region of the LIS. Data consist of previously published (n = 88) and new contributions (n = 39). Results suggest an ice-free HBL during parts of MIS 7, MIS 5 and MIS 3. Radiocarbon, OSL and TL ages form the basis for the MIS 3 assignment. Implies more dynamicity for the LIS than previously modelled for MIS 3.